Développement durable : pourquoi l’homme ne peut pas être seul au centre du concept de "sustainability". Le point de vue d’écologues marins - Gérard Bellan; Jean-Claude Dauvin; Denise Bellan-Santini (Développement Durable et Territoires)
The French translation, “développement durable”, of the English expression, “sustainable development”, defines a mode of development intended to meet the needs of the present generations without compromising the ability of future generations to meet their own needs. This definition appears to us to be very biased. The objective of this paper is to provide the point of view of marine ecologists on the concept of sustainable development. In this paper, we explore in succession: the authors’ own definition compared with the one used in the social sciences, the identification of the coastal seas, their problems, and risks and stakes that confront them, and the requirements for a sustainable development of the coastal marine ecosystems. In conclusion, we highlight the difficulties encountered in meeting the requirements of sustainable development at sea, due to insufficient knowledge and the very relative interest given the sea by the French political authorities and institutional stakeholders.